When and why empowering leadership increases followers’ taking charge: A multilevel examination in China - Li, Shao-Long; He, Wei; Yam, Kai Chi; Long, Li-Rong (Asia Pacific journal of management, 2015)
Drawing from the cultural self-representation model, we propose a multilevel model to examine when and why empowering leadership elicits followers’ taking charge behaviors in China. Data from 310 full-time employees in 81 work groups provide support for the mediating role of role breadth self-efficacy in transforming team-directed empowering leadership into individual taking charge behaviors. In addition, this mediation relationship is found to be attenuated by high differentiated empowering leadership and low individual power distance orientation. Finally, we find support for a three-way moderated mediation—which the moderating effect of differentiated empowering leadership is found to be significant only among followers who have low power distance orientation. We conclude by discussing the theoretical and practical implications of these findings.